DTA measurements in the ternary Ag-Au-Ga system (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
In this work, the ternary Ag-Au-Ga system was studied experimentally by differential thermal analysis (DTA). Measurements were carried out along two chosen cross-sections determined by the ratio of mole fractions XAg/XGa=1:1 and XAu/XGa=1:1 by applying Pegasus 404 apparatus form Netzsch. Experiments were performed at three rates: 1 K min-1, 5 K min-1 and 10 K min-1. Next, the obtained experimental results were used to estimate the temperatures of liquidus by applying extrapolation to zero rate. Moreover, the temperatures of invariant reactions and other phase transformations were investigated from DTA measurements which were carried out with the rate 1 K min-1. Finally, the experimental results were compared with the isopleths obtained from prediction and calculation of the phase diagram which were done by using CALPHAD method. Experimental data obtained in this work are in good agreement with the results of calculation.